Protection and Analysis of 37 Historical Buildings in Cantonese Traditional Villages of Cuiwei Village in Zhuhai - Junzhang Chen; Yile Chen; Liang Zheng (PT FORMOSA CENDEKIA GLOBAL, 2022)
With the rapid development of China's economy, the urbanization process is gradually accelerating, and there are a large number of traditional village spaces are abandoned and compressed, which has greatly changed the original pattern of ancient villages. Cuiwei village is an example of Zhuhai's typical Lingnan Cantonese traditional village evolving into a village in the city, which has experienced many changes in spatial pattern. This paper adopts the method of qualitative investigation to conduct a detailed investigation and analysis of the types of historical buildings in Cuiwei village, and focuses on the impact of historical buildings on people's spatial feelings. It puts forward planning suggestions to provide reference for the follow-up protection of the architectural heritage of Cantonese traditional villages.